Syria Burning : A Short History of a Catastrophe - Glass, Charles and Cockburn Patrick (London Verso, 2016)
"What are the origins of the Syrian crisis, and why did no one do anything to stop it? Since the upsurge of the Arab Spring in 2011, the Syrian civil war has claimed in excess of 200,000 lives, with an estimated 8 million Syrians, more than a third of the country's population, forced to flee their homes. Militant Sunni groups, such as ISIS, have taken control of large swathes of the nation. The impact of this catastrophe is now being felt on the streets of Europe and the United States. Veteran Middle East expert Charles Glass combines reportage, analysis, and history to provide an accessible overview of the origins and permutations defining the conflict. He also gives a powerful argument for why the West has failed to get to grips with the consequences of the crisis"
Include Maps
Keywords: Syria -- Arab Spring (2010-) -- Civil War (Syria : 2011-) -- IS (Organization)